2023
DOI: 10.34172/jcs.2023.30626
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Challenges of Intensive Care Nurses During the COVID-19 Pandemic: A Qualitative Study

Abstract: Introduction: The coronavirus disease 2019 (COVID-19) has been spreading rapidly as a pandemic and posed numerous challenges to healthcare workers (HCWs), especially nurses. This study aimed to investigate the occupational challenges experienced by intensive care unit (ICU) nurses in caring for patients with COVID-19. Methods: This qualitative study was conducted using a conventional content analysis method in September and October 2020. The study environment was the ICU wards dedicated to the patients of COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…In line with the results of the present study, other studies have shown that nurses may not be prepared to communicate with dying patients and their families, 22 , 23 and they may become stressed and fear observing dying patients. 24 Studies conducted during previous pandemic consistently highlight that a relevant proportion of nurses is at risk for developing post-traumatic stress disorder symptoms. 25 The development of post-traumatic stress distress among nurses represents a crucial issue, since the impact of traumatic experiences may have significant long-lasting effects.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the results of the present study, other studies have shown that nurses may not be prepared to communicate with dying patients and their families, 22 , 23 and they may become stressed and fear observing dying patients. 24 Studies conducted during previous pandemic consistently highlight that a relevant proportion of nurses is at risk for developing post-traumatic stress disorder symptoms. 25 The development of post-traumatic stress distress among nurses represents a crucial issue, since the impact of traumatic experiences may have significant long-lasting effects.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Lack or inadequacy of medical facilities, lack of personnel, unpredictable nature of the disease, widespread transmission of the virus, fear of contracting the disease and transmitting it to others, increased working hours, work pressure (physical and emotional), burnout, disruption in service delivery and Changing to telemedicine has been one of the challenges. [7][8][9][10][11] Immediately after the announcement of the COVID-19 pandemic, mandatory restrictions were imposed on providing midwifery care in hospitals and health centers. The primary goal of these mandatory measures was to reduce the transmission of the virus by reducing physical contact.…”
Section: Introductionmentioning
confidence: 99%
“…17 According to studies, in addition to the fear of contracting the disease and the risk of its transmission to family members, lack of protective facilities, lack of access to diagnostic tests for screening, feelings of insufficient support, settling in a new and unfamiliar unit, compliance with rapid changes in guidelines were among other challenges that could lead to a decrease in the quality of midwifery care services. 7,18 On the other hand, many changes were made in the way healthcare services were provided, which included social distancing measures, postponing unnecessary surgeries, avoiding unnecessary referrals, and performing some healthcare operations online. 19 Pregnancy and childbirth care significantly changed under these conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations